3D macroporous CUPC/g-C3N4 heterostructured composites for highly efficient multifunctional solar evaporation. Issue 37 (13th September 2022) - Chu, Cong; Jia, Zhikai; Yu, Yu; Ding, Kejian; Wu, Songmei
Abstract : Solar-driven multifunctional interfacial evaporation is a promising technology for water recycling and purification. Abstract : Solar-driven interfacial evaporation is a promising technology for water recycling and purification. A sustainable solar evaporation material should have not only high photothermal conversion efficiency, but also an ecofriendly fabrication process as well as pollutant degradation and sterilization properties. We present in this work a solar evaporator based on graphitic carbon nitride (g-C3 N4 ) and copper phthalocyanine (CUPC) composites with typical type-I heterojunctions. Superhydrophilic three-dimensional macroporous g-C3 N4 was obtained by self-assembly of precursors in aqueous solution followed by thermal polycondensation. By adding various weight ratios (0.15%, 1.5% and 7.5%) of CUPC, the composites exhibited a strong absorption in the region of red and infrared light. The CUPC–CN 7.5% composite achieved a photothermal conversion efficiency of 98.5% in nanofluids with an interfacial solar evaporation efficiency of 93.6% for artificial sea water and 98.7% for deionized water, which are among the highest reported to date. Besides, the composite materials demonstrated superior water purification capabilities by decomposing dye molecules and E. coli bacteria in aqueous solution. Our work established a novel approach for the development of multifunctional interfacial evaporators based on macroporous organic semiconductor heterostructures.